(untitled) (Conversatoria Linguistica, 2019)
Two American 20th century novels by American George R.R. Martin, namely „A Game of Thrones” (1996) and „A Clash of Kings” (1999) are original, literary paraphrases of Flaubert’s bovarism. The article presents a few theories of bo-varism, a literature review and particularly the conception of love, longing and dreams. This article describes literary transposition of bovarism with regard to Sansa Stark, the heroine of American novels. Sansa Stark’s existence can be reduced to a few, important aspects of the analysed phenomenon such as: suffering from bovaristic hunger of sensual and psychical impressions (intensified by reading romance novels, for example „Song of Florian and Jonquil”), unquenchable desire to be somewhere else that real–time location, existential disappointment, longing for another, better world identified with King’s Landing, producing fantasmatic sensations. As far as Sansa Stark is concerned, she is a neurotic and bored heroine, what draws her closer to Madame Bovary.